1990
DOI: 10.1190/1.1442937
|View full text |Cite
|
Sign up to set email alerts
|

Ground roll: Rejection using polarization filters

Abstract: Ground roll noise on land data sets overwhelms the desired reflection seismic signal unless special steps are taken in data acquisition and processing to control it. This is usually done in the field by the design of group arrays for data acquisition. On the other hand, if multicomponent data are acquired, it is possible to remove ground roll during processing using polarization analysis. Even though this processing is computation-intensive, the potential exists for obtaining results similar to conventional da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
19
0

Year Published

1995
1995
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(19 citation statements)
references
References 13 publications
0
19
0
Order By: Relevance
“…Akal and Berkson 1986, Rauch 1986, Stoll 1989, and Hovem et al 1991 present reviews or collections of articles on aspects of the subject. The greatest advances appear to have been in the use of interface waves to estimate shallow s h e a r v elocities, which is perhaps ironic given the pains taken to lter out these waves in land surveys e.g., Saat cilar and Canitez, 1988;Hermann and Russell, 1990;Shieh and Herrmann, 1990;Blonk, 1995;Ernst and Herman, 1998. In a marine setting, the waves trapped near the solid-uid interface are sometimes called Scholte waves Scholte, 1958, in contrast with Stoneley waves near a solid-solid interface or Rayleigh waves near the air-solid interface. All of these waves, however, are dispersive with phase and group velocities that are sensitive primarily to shear velocities at depths that are inversely related to frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Akal and Berkson 1986, Rauch 1986, Stoll 1989, and Hovem et al 1991 present reviews or collections of articles on aspects of the subject. The greatest advances appear to have been in the use of interface waves to estimate shallow s h e a r v elocities, which is perhaps ironic given the pains taken to lter out these waves in land surveys e.g., Saat cilar and Canitez, 1988;Hermann and Russell, 1990;Shieh and Herrmann, 1990;Blonk, 1995;Ernst and Herman, 1998. In a marine setting, the waves trapped near the solid-uid interface are sometimes called Scholte waves Scholte, 1958, in contrast with Stoneley waves near a solid-solid interface or Rayleigh waves near the air-solid interface. All of these waves, however, are dispersive with phase and group velocities that are sensitive primarily to shear velocities at depths that are inversely related to frequency.…”
Section: Introductionmentioning
confidence: 99%
“…Because of its dispersive nature and low velocity, ground-roll masks the shallow reflections at near offsets and deep reflections at far offsets (Henley, 2003;McMechan and Sun, 1991;Canitez, 1988, 1994) and also distorts reflection events by interfering with them. Some researchers have shown that ground-roll can be attenuated during data acquisition by proper acquisition design and filtering (Holzman, 1963;McKay, 1954;Shieh and Herrmann, 1990). Unfortunately, suppressing the noise with such a strategy may lead to an unacceptable deterioration of reflection events (Coruh and Costain, 1983) and may also have geographical or logistical limitations.…”
Section: Introductionmentioning
confidence: 97%
“…Numerous authors have been shown that the effect of ground roll can be reduced by proper acquisition design and filtering (Brown and Clapp, 2000;Shieh and Herrmann, 1990). Unfortunately, these methods may either fail to remove all the ground roll or may lead to unacceptable deterioration of the primary reflections.…”
Section: Introductionmentioning
confidence: 98%